2018
DOI: 10.1111/tid.12893
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of post‐prophylaxis cytomegalovirus infection in lung transplant recipients

Abstract: Cytomegalovirus (CMV) disease has been associated with the development of chronic lung allograft dysfunction (CLAD) after transplantation. However, the relevance of CMV replication occurring after the discontinuation of antiviral prophylaxis on the development of CLAD has not been fully established. Patients who underwent lung transplantation during 2004-2014 were included. All patients received antiviral prophylaxis for 3-6 months, followed by monitoring of CMV replication during the first year post-transplan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 23 publications
5
12
0
Order By: Relevance
“…Palmer et al 28 found no differences in overall BOS development. This was corroborated in a recent study of the Swiss cohort showing no impact of CMV on CLAD 29 . We must interpret our data with caution, as CLAD usually develops later in the course of post‐transplant.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Palmer et al 28 found no differences in overall BOS development. This was corroborated in a recent study of the Swiss cohort showing no impact of CMV on CLAD 29 . We must interpret our data with caution, as CLAD usually develops later in the course of post‐transplant.…”
Section: Discussionsupporting
confidence: 89%
“…This was corroborated in a recent study of the Swiss cohort showing no impact of CMV on CLAD. 29 We must interpret our data with caution, as CLAD usually develops later in the course of post-transplant. Since our latest patient included was transplanted in December 2017, we were unable to do analyses of CLAD incidence beyond one year after transplantation.…”
Section: Discussionmentioning
confidence: 87%
“…Those immunomodulatory effects of CMV may predispose patients to opportunistic infections, in particular fungal infections (101,108,109). The use of universal antiviral prophylaxis in the current era seems to reduce the impact of CMV in allograft outcomes (110,111).…”
Section: Cytomegalovirusmentioning
confidence: 99%
“…Without a preventive strategy, CMV infection and disease typically occur during the first three months after transplantation (93). Current incidence of CMV disease in lung transplant recipients varies from 5% to 40% depending on serological status and preventive strategy used (111)(112)(113). The main preventive strategies against CMV disease are antiviral prophylaxis and preemptive approach.…”
Section: Cytomegalovirusmentioning
confidence: 99%
“…In a cohort of lung transplant recipients who received CMV prophylaxis for 3 to 6 months, followed by monitoring and preemptive therapy, neither CMV infection nor CMV disease had a significant impact on long-term allograft lung function. 246 Community-acquired respiratory viruses (CARVs) have also been implicated in CLAD, especially in patients who develop lower respiratory tract infections. 80 In one observational study that categorized viral infections based on the presence or absence of pneumonia, only those with pneumonia had an increased risk for CLAD.…”
Section: Infectious Factorsmentioning
confidence: 99%